If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -18 = 90 Reorder the terms: -18 + 6x = 90 Solving -18 + 6x = 90 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '18' to each side of the equation. -18 + 18 + 6x = 90 + 18 Combine like terms: -18 + 18 = 0 0 + 6x = 90 + 18 6x = 90 + 18 Combine like terms: 90 + 18 = 108 6x = 108 Divide each side by '6'. x = 18 Simplifying x = 18
| 6(n-1)=7n-8 | | (10n-5)/5 | | 9+-27=x | | 13+15=x | | 5/4x-12=2x | | 68x-85=17(4x-5) | | 5x+7=8x-4x | | 2(y+2)+y=19-2y+3 | | 6x+3x-7x+4=10 | | (3x-4)(3x+5)=0 | | 4.8*15=72 | | -4-7=x | | (1/2x+3)=125 | | 6x^2+4x-2=52 | | 4.8*15= | | 9x+2=8x+7 | | 3x+2y-5+3y-2x= | | 15x+2=7x+4 | | 18k^2-12k=2+4k^2 | | 3/5y=2/3y+9 | | 2x+3-x= | | ax-bx=15forx | | 19-21=x | | (a+bi)(6-7i)=53+9i | | 4x-8=2x-18 | | 5(x-3)=2x+2(x-5) | | 5/8(12+3x)=15 | | 33x+57=33x+61 | | -5(2n-3)-6=3(5n+1)-8 | | ax-bx=15 | | 7-2x=6x-30 | | 11x-21=5+7x |